A Technique to Obtain Stable Centric Occlusion Records Using Impression Plaster - Kostas Stamoulis, DDS, Phd; and Andrew Eleftherios Hatzikyriakos, DMD, PhD (Journal of Prosthodontics, 2007)
Recording the maxillomandibular relationship is often a challenge